The Analysis of Factors Affecting the Quality of Local Government Financial Reports in Karangasem Regency - Ratih Manuari Ida Ayu; Widya Wati Ni Putu; Cahyadi Putra I Gede (AIBPM Publisher, 2025)
Government financial reports are essentially a form of accountability by the government to the public regarding the management of public funds, whether from taxes, levies, or other transactions. As we know, financial reports serve as a medium for an entity, in this case, the government, to account for its financial performance to the public. This study aims to analyze the influence of leadership ethics, human resource competence, employee commitment, accounting knowledge level, and the role of supervisory bodies on the quality of local government financial reports in Karangasem Regency. The sample used in this study consisted of 25 Government Work Units (SKPD) in Karangasem Regency with 99 respondents. The sampling technique used in this study was purposive sampling. The data analysis technique employed was multiple linear regression analysis. The results show that leadership ethics, human resource competence, and the role of supervisory bodies have a positive impact on the quality of financial reports, while employee commitment and accounting knowledge level do not have a significant effect on the quality of financial reports. Future research could develop this study by using other variables that theoretically influence the quality of financial reports, such as government accounting standards (SAP).